Methodology for Identifying the Differentiated Mineral Extraction Tax Rates Relating to the Recovery of Solid Minerals - BLOSHENKO, Tatiana Alekseevna; PONKRATOV, Vadim Vitalievich; POZDNYAEV, Andrey Sergeevich (Journal of Environmental Management and Tourism; Vol 8 No 1 (2017): JEMT Volume VIII Issue 1(17) Spring 2017, 2017)
The paper presents the methodology for identifying the differentiated Mineral Extraction Tax ( MET ) rates relating to the recovery of solid minerals. Experiments, aimed to find solutions to these tasks by using generalized gradient method, have shown that the objective functions may have more than one local extremum. In this respect, to calculate ad valorem MET rates, it is suggested to use evolutionary algorithms. The technogenic raw materials are currently of economic interest for the purpose of extraction of valuable components and production of finished goods. Moreover, sometimes the content of valuable components in technogenic deposits (TD) exceeds their content in natural fields to be processed. Secondary mineral resources bring harm to the ecosystem, yet it is impossible to insure the environmental risks due to the lack of objects of subsoil use. The differentiated rates are selected on the basis of maximum MET capacity on all the valuable components extracted from deposits provided that each deposit is considered to be an investment project for the stated problem.